Pengaruh Profitabilitas, Likuiditas, Solvabilitas, Ukuran Perusahaan, terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI - Daffa Adhyasta; Sri Sudarsi (Ekonomis: Journal of Economics and Business, 2023)
This study aims to examine and analyze the effect of profitability (ROA), liquidity (CR), solvability (DR), and firm size (SIZE), on firm value (Tobin's Q). The population used in this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in three periods, namely 2019-2021. The sampling method used in this study was purposive sampling, so that a total of 332 samples were obtained. The analytical method in this study is multiple linear regression analysis using IBM SPSS 22 software. The results of this study indicate that profitability (ROA), ), liquidity (CR), solvability (DR), and firm size (SIZE) have a positive and significant effect on firm value (Tobin's Q).